Morphophysiology of Punica Granatum L. under microalgae biomass stimulation - Gomes, fernando antonio lima; Araújo, Railene Hérica Carlos Rocha; Nóbrega, Jackson Silva; Linné , Jéssica Aline; Teodosio , Albert Einstein Mathias de Medeiros; Santos , Adriana da Silva; Silva, Márcio Santos da; Lima, José Franciraldo de (Comunicata Scientiae, 2024)
The use of microalgae has been proeminent in agricultural scenario, because it is an alternative product considered extremelly productive, which contains essential elements for plants. Thus, this study aimed to evaluate the morphophysiology of Punica granatum L. seedlings treated with Spirulina platensis and Scenedesmus sp. nanoparticles in controlled environment. The research was carried out at the of Federal University of Campina Grande, Pombal-PB, using a completely randomized design with five replications. The factorial scheme (2 x 4) was adopted, represented by two types of microalgae (Spirulina platensis; Scenedesmus sp.) and four doses of application (0, 5, 10 and 15%). Growth evaluations happened at 135 days after planting, verifying the number of leaves and branches and shoot length. The physiological parameters evaluated were gas exchanges, chlorophyll ‘a’ fluorescence, electron transport rate, stationary fluorescence, maximum fluorescence yield after light adaptation and quantum efficiency of PSII. Shoot length and number of branches had rises at doses of 6 and 15%. Number of leaves was induced in seedlings at dose of 8% with Spirulina platensis. Stomatal conductance and internal CO2 concentration increased in seedlings sprayed with Spirulina platensis. extract of Scenedesmus sp. improved the stationary fluorescence and quantum efficiency of PSII in pomegranate seedlings.